The Role of Instructional Designers in the Integration of Generative Artificial Intelligence in Online and Blended Learning in Higher Education - Kumar, Swapna; Gunn, Ariel; Rose, Robert; Pollard, Rhiannon; Johnson, Margeaux; Ritzhaupt, Albert (Online Learning, 2024)
The purpose of this exploratory research study was to examine the roles instructional designers (IDs) in higher education play in the integration of generative Artificial Intelligence (GenAI) into their organizations, and how they use GenAI technologies in their own professional practices. Data were collected from 15 participants in the southeastern United States (U.S.) in an ID role or with similar job titles (e.g., educational technologist). Using a general qualitative approach, semi-structured interviews were conducted in Zoom about IDs’ use and integration of GenAI. Our findings resulted in three primary themes related to IDs’ integration of GenAI in online and blended education: (a) use of GenAI for instructional design; (b) collaborative guidance for faculty integration of GenAI; (c) training, resources, and guidelines on the integration of GenAI. A common thread through all the themes and interviews was IDs’ conscientious and cautious approach and ethical concerns about GenAI integration. We unpack these themes while discussing the implications of IDs in higher education integrating GenAI to meet organizational, faculty, and student needs. We provide limitations and a rich discussion about the advancement of GenAI by IDs working in institutions of higher education.